Efeito da carnosina no controle da formação de N-nitrosaminas em produtos cárneos curados - Scheeren, Marina Bergoli (2016)
The objective of this study was to evaluate the effect of the addition of carnosine (4.5 g/kg) on the control of N-nitrosamines formation in cured meat products, compared with sodium erythorbate (0.5 g/kg) and the combination of both. First an alternative analytical method for measuring trace amounts of nine volatile N-nitrosamines in different types of cured meat products by gas chromatography-chemical ionisation/mass spectrometry (GC-CI/MS) in positive-ion mode using methanol as reagent was successfully developed and validated. Then, N-nitrosamines quantification was conducted in two model systems developed in this study: the first was performed in buffer solution at pH 5.6 (meat pH); the second was carried out in meat matrix and some technological properties were evaluated in the products. Carnosine added alone or in combination with sodium erythorbate promoted an increase of about 0.2 units of pH values in meat samples, while adding sodium erythorbate alone showed no differences compared to control (without addition of antioxidants). Higher values of water retention during cooking in treatments where carnosine was added, clearly indicate the effect of pH on these results, as well as a reduction in L* and b* color values might be related to an increase on the water retention and hence the water-soluble pigments retention. Antioxidant activities of carnosine and sodium erythorbate were evaluated and the results indicated that antioxidant capacity of sodium erythorbate (77.78 to 78.75%) was superior to that of carnosine (0.00-53.60%). In the curing solution both erythorbate and carnosine had a positive effect on the inhibition of NAs formation and the superior inhibiting effect of erythorbate was explained by its higher ability to reduce N2O3 and NO+ to NO in the presence of oxygen, contributing to its superior effect when heat process was applied. On the contrary, in meat samples stored in the presence of oxygen, sodium erythorbate contributed to an increase in NAs concentration with respect to the control that is likely attributable to its higher initial NO formation and its consumption for metmyoglobin reducing reactions during storage time. Added carnosine brought this increased NAs formation by erythorbate to the level found in the control. The difference in NAs formation between the two models can be explained by the presence of myoglobin in the meat system making a demand on available erythorbate. The combined information from the two systems indicates that carnosine offers an added protection for NAs inhibition in condition of excess formation.